The Effect of Lactic Acid Hydrolysis in the Making of Modified Maizena Flour - Yudanto, Yusuf Arya; Alvina, Raissa Wahyu; Pudjihastuti, Isti (Journal of Vocational Studies on Applied Research, 2020)
Flour is a useful agricultural product for various foodstuffs, one type of flour obtained in Indonesia is wheat flour. The need for this flour makes the import number of Indonesia increase, whereas many other plants have great potential to be used as raw material for making flour, such as tubers, taro, corn, and others. However, the content of amino acids and sugar as an energy source in corn is still relatively low. So we need a breakthrough to improve it and can affect the quality of the final product. This experiment focused on the combination of the lactic acid hydrolysis process in addition to UV light on maize starch so that the modified product is expected to have properties that almost the same with flour. There is a variety of changing variables which is the concentration of lactic acid. The number of the concentration that we use for this research is 0.5% (w/v); 1% (w/v); 1.5% (w/v); and 2% (w/v). The score of water content that we get is decreasing. It happened because the lactic acid can weaken hydrogen bonds which causes starch molecular weight to be lower, the structure becomes tenuous and soft, so that more water is evaporated during the oven drying process. Besides, the length of the hydrolysis process also affects the water content of the flour produced, which is soaking time inversely proportional to the water content produced. This happens because the longer the reaction with lactic acid causes the hydrogen bonds in starch to be weak so that the bonds between water molecules with various other components in the material more easily broken. From the analysis, the best point of the water content and baking expansion is consequently 18.780% and 40%. From 4 concentrations used (0.5%; 1%; 1.5%; and 2%), the lowest concentrations gave the best result, because it got the highest score in the baking expansion. This research result shows that modified starch has a better characteristic than natural starch. The factor that determined the good flour is the rheology characteristic which is the baking expansion.